Brancusi and His Poets - Joshua S. Mostow (Studies in 20th & 21st Century Literature, 1985)
This article examines four poems on the work of the modern sculptor Constantin Brancusi, written between 1922 and 1966 by four different poets: Carl Sandburg, Mina Loy, Jean (Hans) Arp, and Jiri Kolar. The purpose of the article is to explore how the varying poetics of these writers—the modernism of the Chicago Renaissance, Futurism, Dadaism, and Concrete poetry—influenced the poets' reception and interpretation of the sculptor and his work. This study approaches the relations between visual and verbal art through a semiotic methodology, and while the discussion of the poems takes the form of comparative literature, the main concern of the essay is a Rezeptionsgeschichte of Brancusi's work. This reception has had a direct influence on twentieth-century literature due to the importance of visual art theories and programs for the poetry of the time. Brancusi's work serves as a constant and as a tool with which to examine and articulate the differences between these four important literary movements.
Keywords: poem; modern; sculptor; Constantin Brancusi; Carl Sandburg; Mina Loy; Jean (Hans) Arp; Jiri Kolar; modernism; Chicago Renaissance; Futurism; Dadaism; Concrete poetry; visual; verbal; semiotic methodology; comparative literature; Rezeptionsgeschichte; twentieth-century; literature; visual art theories